Musculoskeletal screening to identify female collegiate rowers at risk for lo back pain - Gonzalez, S. L.; Diaz, A. M.; Plummer, H. A.; Michener, L. A. (Journal of Athletic Training, 2018)
Context Rowers are at risk for overuse injuries, including low back pain (LBP). Defining the utility of screening tests for identifying those at risk for LBP can aid in the development of guidelines for injury prevention.